Accelerated wound repair, cell proliferation, and collagen accumulation are produced by a cartilage-derived growth factor (The Rockefeller University Press, 1985)
Cartilage-derived growth factor (CDGF), a cationic polypeptide of approximately 18,000 mol wt, was prepared from bovine articular cartilage; other sources were bovine and human scapular and costal cartilage. Previous studies have shown that CDGF stimulates the proliferation of cultured mouse fibroblasts as well as chondrocytes and endothelial cells from various sources. In this study, CDGF was shown to stimulate dose-dependently the accumulation of DNA and collagen by rat embryo fibroblasts and a population of fibroblasts derived from granulation tissue. CDGF also stimulated the proliferation of cultured bovine capillary endothelial cells dose-dependently. To evaluate the effects of CDGF in vivo, we implanted polyvinyl alcohol sponges subcutaneously in rats. 6 d postimplantation, sponges were injected with 300 micrograms of partially purified CDGF, a dose which takes into account the cell numbers in the sponges as compared with cell cultures. CDGF rapidly disappeared from the sponges and only approximately 10% of the initial dose was present at 4 h. Despite its transient presence, CDGF caused a relative increase in sponge DNA content of 2.6-fold at 48 h and 2.4-fold at 72 h. We repeated the sponge experiment by using 500- ng injections of CDGF purified to near homogeneity by heparin-Sepharose chromatography. Purified CDGF caused significant increases in sponge collagen, protein, and DNA content at 48 and 72 h after a single injection. The effects of CDGF were abolished by heat and unaffected by reduction of disulfide linkages. Morphologically, CDGF did not evoke an inflammatory response, and its effect on proliferating endothelial cells and fibroblasts was, therefore, probably direct. However, increases in DNA content of sponges could not be fully accounted for by increased DNA synthesis, which suggests that recruitment may be an important component of the in vivo response. Taken together, the effects of CDGF on cultured cells and granulation tissue suggest that the sustained presence of CDGF in vivo may greatly enhance its effects upon wound repair.